A Spatial Exploration of Political Stability, Investment, and Economic Prosperity in Africa - Karim, Mohamed; Simoh, Mohamed; El Baraka, Hamza; El Yazidi, Mohammed; Mouhil, Ismail (International Journal of Economics and Financial Issues, 2024)
The intricate dynamics between political stability and economic growth have emerged as a central focus of scholarly inquiry and policy consideration. This study delves into the nuanced relationship between political stability, investment, and economic prosperity within the unique context of African nations. Theoretical perspectives on this relationship range from negative to positive, reflecting the complexity of the interplay between political environments and economic trajectories. Drawing on a panel of 48 African countries spanning the years 2000-2020, this study employs a sophisticated generalized method of moments-type estimator for linear dynamic panel data models. Unlike many previous studies, we explicitly address the significance of institutional structures and their role in shaping economic growth dynamics. Our findings reveal that political stability is a key determinant with a structurally significant impact on economic growth. Moreover, the study highlights the catalyzing effect of investment, demonstrating a significantly positive influence on economic growth in politically stable environments.